Ensuring Ukraine's security: From ad hoc support to long-term security guarantees as NATO member - Margarete Klein; Claudia Major (Stiftung Wissenschaft und Politik (SWP), 2023)
Since February 2022, Ukraine has been defending itself against yet another Russian war of aggression. Now that immediate support - military, diplomatic, financial and humanitarian - for Ukraine has improved, the country's long-term security needs to be addressed. Looking ahead, security commitments should be built on political, economic and military pillars. NATO membership is essential for Ukraine's security, but it is also in the geostrategic and normative interests of the Alliance, even if it is a risky, long-term and difficult endeavour. At the 2023 summit in Vilnius, NATO recognized that Ukraine's future is in the Alliance but remained vague about the conditions to join. Yet, other agreements announced on the margins of the summit by the G7 and individual states expand the support for Ukraine. Framed as steps to increase Ukraine's security, these should accompany the transition from current security support to future guarantees.
Keywords: 320; Ukraine; Russian war against Ukraine; security commitments; security guarantees; Ukraine’ s NATO accession; NATO; Nato; 2023 Vilnius summit; 2023 NATO summit; EU; European security; Kyiv Security Compact